Legal Dimensions of Online Business and Retailing: A Comprehensive Dataset - Herlina Oktavia; Noor Fatimah Mediawati; Dewi Rositasari (Proceedings of The ICECRS, 2023)
In this data article, we aimed to identify and collect relevant literature on the subject of "Online Business" and "Retailing" using keyword-based searches on the lens.org website. Employing filters for document types such as "Journal Article" and "Conference Proceeding," as well as the "Law" subject matter, we refined our search to yield 553 documents. The results provide a comprehensive foundation for researchers and scholars interested in exploring the intersection of online business and retailing from a legal perspective. This dataset, comprising 553 articles, is a valuable resource for understanding the legal dimensions of online business and retailing, facilitating future research and literature reviews in this domain.Highlights: Comprehensive Dataset: The collection of 553 articles on online business and retailing, filtered by the "Law" subject matter, offers a comprehensive resource for researchers, providing insights into the legal dimensions of this evolving field. Interdisciplinary Relevance: This dataset bridges the gap between online business, retailing, and legal studies, facilitating interdisciplinary research and offering valuable insights into the complex relationship between e-commerce, commerce, and the law. Research Catalyst: The dataset serves as a catalyst for further exploration and research, empowering scholars to delve deeper into the legal implications of online business and retailing, ultimately advancing our understanding of this dynamic and vital industry. Keywords: Online Business, Retailing, Legal Perspective, Research Dataset, Literature Review